Investigation of drug-related problems in patients hospitalized in chest disease wards: A randomized controlled trial - SANCAR, MESUT (My University, 2023)
Copyright © 2023 Bektay, Sancar, Okyaltirik, Durdu and Izzettin.Objective: According to the World Health Organization (WHO), chest diseases are among the 10 diseases that cause the highest mortality worldwide. Drug-related problems (DRPs), readmission, and antimicrobial resistance are critical problems in chest disease wards. Active involvement of clinical pharmacists (CPs) who are focused on reducing the risks of potential problems is needed. The aim of this study is to investigate the effects of pharmaceutical care (PC) services on the pulmonology service. Method: A randomized controlled trial at a university hospital in Istanbul was conducted between June 2020 and December 2021. The participants were randomized into the control group (CG) and intervention group (IG). In the CG, CPs identified and classified the DRPs according to Pharmaceutical Care Network Europe v9.0 (PCNE) and provided solutions to DRPs for the IG. The effect of PC services was evaluated by the number and classification of DRPs, and readmissions within 30 days were compared between the two groups. Results: Out of 168 patients, 82 were assigned to the IG. The average number of medicines administered per patient in the CG and IG was 14.45 ± 7.59 and 15.5 ± 6.18, respectively. In the CG and IG, the numbers of patients with DRPs were 62 and 46, respectively. The total number of DRPs was 160 for CG and 76 for IG. A statistically significant difference was found in favor of the IG, in terms of the number of patients with DRPs, the total number of DRPs, and readmission within 30 days (p < 0.05). Conclusion: In this study, CP recommendations were highly accepted by the healthcare team. Pharmaceutical care services provided by CPs would decrease possible DRPs and led to positive therapeutic outcomes. Cognitive clinical pharmacy services have beneficial effects on health care, and these services should be expanded in all settings where patients and pharmacists are present.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji; Farmakoloji (tıbbi); Pharmacology; Pharmacology (medical); chest diseases; clinical pharmacist; cognitive pharmacy services; drug-related problems; pharmaceutical care